The SAGE handbook of architectural theory - Crysler, C. Greig (Christopher Greig); Cairns, Stephen; Heynen, Hilde (Los Angeles ; London ; New Delhi ; Singapore ; Washington DC : SAGE Publications, 2012)
Now available in paperback, this is a cutting edge, detailed and comprehensive exploration of architectural theory. Its focus on interdisplinarity and cross-cultural ties ensures the discipline's relationship with the social sciences is fully explored.
Introduction - 1: Architectural Theory in an Expanded Field - C. Greig Crysler, Stephen Cairns and Hilde HeynenIntroduction - 2: Reading the Handbook - C Greig Crysler, Stephen Cairns, Hilde HeynenPART ONE: POWER/DIFFERENCE/EMBODIMENTIntroduction: Shifting Paradigms and Concerns - Hilde Heynen and Gwendolyn WrightArchitecture, Capitalism and Criticality - Ole W FischerInterrogating Difference: Post-Colonial Perspectives in Architecture and Urbanism - Jyoti HosagraharTendencies and Trajectories: Feminist Approaches in Architecture - Jane RendellSection 1 BibliographyCitizenship - Ines WeizmanPART TWO: AESTHETICS/PLEASURE/EXCESSIntroduction: Architecture and Aesthetics - John Macarthur and Naomi SteadArchitectural Phenomenology and the Rise of the Postmodern - Jorge Otero-PailosFormalism and Forms of Practice - Sandra Kaji-O'GradyArt in (and of) Architecture: Autonomy and Medium - Bart VerschaffelSection 2 BibliographyConsumption - Ana Miljacki PART THREE: NATION/WORLD/SPECTACLEIntroduction: Enacting Modernity - AbdouMaliq SimoneRethinking the Nation - Abidin Kusno Entangled Modernities in Architecture - Duanfang LuNotes on the Society of the Brand - Shiloh Krupar and Stefan Al Section 3 BibliographyHeritage - Fernando DiezPART FOUR: HISTORY/MEMORY/TRADITION Introduction: Time's Arrows: Spaces of the Past - C Greig CryslerPreservation and Modernity: Competing Perspectives, Contested Histories and the Question of Authenticity - Mrinalini RajagopalanCollective Memory Under Siege: The Case of 'Heritage Terrorism' - M Christine BoyerConcepts of Vernacular Architecture - Robert Brown and Daniel MaudlinSection 4 BibliographyCulture - Paul WalkerPART FIVE: DESIGN/PRODUCTION/PRACTICEIntroduction: Architecture's Double-Bind - Dana CuffPrometheus Unchained: The Multiple Itineraries of Contemporary Professional Freedom - Paolo TombesiManners of Working: Fabricating Representation in Digital Based Design - Christopher HightPlural Profession, Discrepant Practices - David SalomonSection 5 BibliographyFlows - Stephen CairnsPART SIX: SCIENCE/TECHNOLOGY/VIRTUALITY Introduction: Technology, Science and Virtuality - Arie Graafland and Heidi SohnVirtual Architecture, Actual Media - N. Katherine Hayles and Todd Gannon Technology, Virtuality, Materiality - Antoine PiconArchitecture, Technology and the Body: From the Pre-Human to the Post-Human - Jonathan HaleSection 6 BibliographyInfrastructure - Delia Duong Ba WendelPART SEVEN: NATURE/ECOLOGY/SUSTAINABILITYIntroduction: Whither 'Earthly' Architectures: Constructing Sustainability - Simon GuyThe Ecology Question and Architecture - Richard IngersollBeyond Sustainability: Architecture in the Renewable City - Peter DroegeTropical Variants of Sustainable Architecture: A Post-Colonial Perspective - Jiat-Hwee ChangSection 7 BibliographyLandscape - Kelly ShannonPART EIGHT: CITY/METROPOLIS/TERRITORYIntroduction: Metropolis, Megalopolis and Meta-City - Brian McGrath and Grahame ShaneThe Contemporary European Urban Project: Archipelago City, Diffuse City and Reverse City. - Paola ViganoSlum as Theory: Mega-Cities and Urban Models - Vyjayanthi RaoCommon Lines of Flight towards the Open City - Deborah NatsiosSection 8 Bibliography Housing - Iain Low
Includes bibliographical references and index.
ARC
Department of Architecture
Keywords: Architecture -- Philosophy; Architecture